2018
DOI: 10.1097/cin.0000000000000449
|View full text |Cite
|
Sign up to set email alerts
|

Use of Communication Tools for Mechanically Ventilated Patients in the Intensive Care Unit

Abstract: The use of light and no sedation is gaining currency in the intensive care unit, resulting in more conscious patients. Due to mechanical ventilation, patients are unable to communicate verbally, and may feel frustration. Communication tools may help; however, they are not used systematically in clinical practice. Based on "complex interventions" and a qualitative approach, a communication tool was modified, tested, and evaluated in this study. The tools consisted of a tablet with communication software and a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 28 publications
0
25
0
1
Order By: Relevance
“…Studies that examined the communication methods used by mechanically ventilated patients reported that unaided approaches mostly encompassed the use of yes/no signals as the dominant strategy and aided AAC was rarely applied (Happ et al., 2011; Sii & Swann, 2015). Unaided AAC may be the dominant approach as mechanically ventilated patients experience a greater level of physical weakness and fatigue and fluctuate in the level of consciousness and/or cognition, thus unable to use advanced AAC (Holm & Dreyer, 2018b; Sii & Swann, 2015). However, in our umbrella review the aided techniques dominated the results concerning AAC.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that examined the communication methods used by mechanically ventilated patients reported that unaided approaches mostly encompassed the use of yes/no signals as the dominant strategy and aided AAC was rarely applied (Happ et al., 2011; Sii & Swann, 2015). Unaided AAC may be the dominant approach as mechanically ventilated patients experience a greater level of physical weakness and fatigue and fluctuate in the level of consciousness and/or cognition, thus unable to use advanced AAC (Holm & Dreyer, 2018b; Sii & Swann, 2015). However, in our umbrella review the aided techniques dominated the results concerning AAC.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who are intubated and remain conscious often have problems communicating their thoughts, feelings and requests to healthcare staff (Holm & Dreyer, 2018; Karlsson et al, 2012; Khalaila et al, 2011). In this study, a web-based communication application was designed for non-speaking patients to facilitate communication with healthcare staff, and this tool was tested with intubated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Attention-seeking actions (Karlsen et al, 2019) Attention-seeking attentions are efforts made to achieve joint attention and understanding from patients Basic communication criteria (Happ, 2021;Holm & Dreyer, 2018b) Basic communication criteria are linked to both physical, sensory and cognitive abilities of the person to communicate coherently.…”
Section: Condensation Of Corementioning
confidence: 99%
“…Communication needs (Fitch et al, 1998;Jansson et al, 2019;Holm & Dreyer, 2018b;Mobasheri et al, 2016) Communication needs are multi-dimensional and include physical, social, emotional and psychological aspects. Can alter depending on the patient's illness trajectory Communication skills (Finke et al, 2008;Holm et al, 2020) Adequate skills in communication are important in the interaction between patients and providers, to be able to understand each other efficiently.…”
Section: Condensation Of Corementioning
confidence: 99%